Diversity of mammals in forest patches of Cisokan, Cianjur, West Java, Indonesia - TEGUH HUSODO; PUPUT FEBRIANTO; ERRI NOVIAR MEGANTARA; SYA SYA SHANIDA; MUHAMMAD PAHLA PUJIANTO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Husodo T, Febrianto P, Megantara EN, Shanida SS, Pujianto MP. 2019. Diversity of mammals in forest patches of Cisokan, Cianjur, West Java, Indonesia. Biodiversitas 20: 1281-1288.  Most species on Java, Indonesia are ecologically associated with or dependent on forests, the island’s high deforestation rates are a major threat to its species. Until now, various efforts to conserve mammals are still focused on natural ecosystems, such as forests. There has not been much research on mammals carried out specifically in non-conservation forest areas, whereas many regions in Indonesia have extensive community lands in the landscape and are directed to be areas that have a conservation function, besides still functioning as a production system. Therefore, it is necessary to examine the diversity of mammals that are still found in Cisokan especially those that have high conservation status and their habitat. Combination of several research methods applied, such as semi-structured interview, sign survey, direct observation, camera trapping, and collapsible trap. Mammalian diversity in the Cisokan forest patched is found in 26 species and among them are endangered species, such as Javan Leopard, Pangolin, and Slow Loris. These three species occupy diverse land cover from natural forest to human lands, such as production forests, settlements, rice fields, and agroforestry or mixed gardens. The existence of these species on human land has the potential for human-wildlife conflict, so it needs to be studied further in wildlife management in Cisokan.